Understanding the linkage between abusive supervision and counterproductive work behavior: the role played by resilience and psychological contract breach - Muhammad Rizwan Sabir; Muhammad Bilal Majid; Muhammad Zia Aslam; Abdul Rehman; Sumaira Rehman (Cogent Business & Management, 2024)
A productive and positive workplace culture is essential to gaining positive organizational work outcomes. At the same time, counterproductive work behaviour in Punjab has been observed as a prevailing negative behaviour that hinders positive workplace behaviour. Counterproductive work behaviour works against organizational goals and is considered one of the negative sides of organizational behaviour. The current research tested the influence of abusive supervision on counterproductive work behaviour with the mediating role of Transactional and relational psychological contract breach. However, this research has also tested Resilience as a moderator-mediator between abusive supervision and the two forms of psychological contract breach. The hypothesized associations among variables were tested through the primary quantitative research method. Convenience sampling under non-probability sampling approach was implemented. Data was collected from 350 Punjab civil secretaries' employees. Three hundred twelve screened and cleaned data were analyzed using SPSS and AMOS. Results declared that Abusive supervision significantly impacts counterproductive work behavior, whereas the mediation moderation of Relational psychological contract breach among all variables has resulted in being insignificant. The mediation of Relational psychological contract breach between Abusive supervision and counterproductive work behavior was significant, while the mediation of Transactional psychological contract breach between Abusive supervision and counterproductive work behavior was insignificant. Resilience resulted as an insignificant mediator moderator in this model The research holds various theoretical and practical implications, and the research limitations have also been addressed.This research examined how abusive supervision can lead to counterproductive work behavior, mediated by relational and transactional psychological contract breaches, and moderated by employee resilience. Data was collected from 350 civil servants in Punjab and analyzed using SPSS and AMOS. Results showed abusive supervision significantly impacted counterproductive work behavior. Relational contract breach mediated the relationship between abusive supervision and counterproductive work, while transactional breach did not. The hypothesized moderated mediation of resilience between abusive supervision, psychological contract breaches, and counterproductive behavior was insignificant. This contributes to theory by testing a model linking abusive supervision, contract violations, and counterproductive behavior, including the role of resilience. For practice, it highlights the need to curb abusive supervision to avoid psychological contract breaches and counterproductive behaviors. Limitations include the cross-sectional design and sampling employees from one region. Future research should use experimental and longitudinal approaches and sample more diverse organizations.
Keywords: 650; Workplace ostracism; abusive supervision; transactional psychological contract breach; relational psychological contract breach; counterproductive work behaviour; resilience